Estrategias pedagógicas para mitigar conductas disruptivas en las estudiantes de 4° en la Institución Educativa Politécnico de Soledad (2019)
The present investigation of quantitative approach has as purpose to define the incidence of pedagogical strategies to reduce disruptive behavior in students of 4th grade of the Polytechnic Educational Institution of Soledad, so that the operationalization of the objectives was performed under the quasi-experimental design. During this process the pre-test and post-test technique was implemented, using the "My behavior questionnaire" and then execute pedagogical intervention strategies in one of the fourth grade groups (experimental group) with the purpose of mitigating the disruptive behaviors they present, and then make a later comparison of the levels of the same with the other group (control group). The statistical results after the intervention to the experimental group show a better performance in the test, with which they have had a growth in relation to the factors evaluated and exceed those obtained by the control group, showing a real change in the disruptive behaviors that this group manifested.